Treatment of moderate-to-severe plaque psoriasis with tildrakizumab in the real-life setting - Martina Burlando; Riccardo Castelli; Emanuele Cozzani; Aurora Parodi (BioExcel Publishing Ltd, 2021)
Background: Tildrakizumab is a high-affinity, humanized IgG1κ monoclonal antibody targeting the p19 subunit of IL-23, which is a key regulatory cytokine in psoriasis. Based on evidence from clinical trials, tildrakizumab is approved for the treatment of moderate-to-severe plaque psoriasis in patients eligible for systemic therapy. Methods: We report our clinical experience with 26 patients followed up to 24 weeks. Results: No adverse event was observed and no patient discontinued tildrakizumab. Whilst no patient had a Psoriasis Area and Severity Index (PASI) score of <5 at baseline, at week 4, 8 (32%) patients had a PASI score of <3 and 6 of these had a PASI score of 0. At week 12, 19 (79%) patients had a PASI score of <5 and, among these, 18 had a PASI score of <3 of whom 16 had a PASI score of 0. At week 24, 22 (96%) patients had a PASI score of <3 and 20 (87%) had a PASI score of 0. Quality of life was improved after 4 weeks and through the whole period of observation. Conclusion: Our experience in the real-life setting confirms the efficacy and safety of tildrakizumab as demonstrated by clinical trials.